Citizen Engagement in Rulemaking : Evidence on Regulatory Practices in 185 Countries - Johns, Melissa (World Bank, Washington, DC, 2016)
This paper presents a new database of indicators measuring the extent to which rulemaking processes are transparent and participatory across 185 countries. The data look at how citizen engagement happens in practice, including when and how governments open the policy-making process to public input. The data also capture the use of ex ante assessments to determine the possible cost of compliance with a proposed new regulation, the likely administrative burden of enforcing the regulation, and its potential environmental and social impacts. The data show that citizens have more opportunities to participate directly in the rulemaking process in developed economies than in developing ones. Differences are also apparent among regions: rulemaking processes are significantly less transparent and inclusive in Sub-Saharan Africa, the Middle East and North Africa, and South Asia on average than in Organisation for Economic Co-operation and Development high-income countries, Europe and Central Asia, and East Asia and the Pacific. In addition, ex ante impact assessments are much more common among higher-income economies than among lower-income ones. And greater citizen engagement in rulemaking is associated with higher-quality regulation, stronger democratic regimes, and less corrupt institutions.